Is There a Place for Immunotherapy for Metastatic Microsatellite Stable Colorectal Cancer? - Ghiringhelli, François; Fumet, Jean-David (Frontiers in Immunology, 2019)
Immunotherapy using checkpoint inhibitor targeting PD-1 and PD-L1 revolutionized the treatment of microsatellite instable metastatic colon cancer. Such treatment is now a standard of care for these patients. However, when used as monotherapy checkpoint inhibitors targeting PD-1 and PD-L1 are not effective in metastatic colorectal cancer patients with microsatellite stable tumors. Recent advances in biology provide a rationale for this intrinsic resistance and support the evaluation of combination therapy to reverse resistance. This article will highlight recent findings on the mechanism of intrinsic resistance and recent advances in clinical trials for combination-therapy.